KONJUNGSI BAHASA INDONESIA DALAM MAJALAH DARING JENDELA PENDIDIKAN DAN KEBUDAYAAN EDISI 45 JULI 2020 - Firman Tara; Nuraeni Nuraeni (Universitas Batanghari, 2021)
This research aims to describe the types of coordinative conjunctions and subordinate conjunctions in the online magazine Jendela Pendidikan dan kebudayaan 45th July 2020. The method used in this research is the qualitative descriptive method. This research's data is in the form of sentence excerpts containing coordinative conjunctions and subordinate conjunctions in an online magazine. The data source is a document from the 45th edition, July 2020 issue of Jendela Pendidikan dan Kebudayaan magazine. The data collection techniques used is documentation. Data analysis was conducted by using Chaer theory (2015) related to coordinative conjunctions and subordinate conjunctions. The results show nine types of coordinative conjunctions including (summation, selection, opposition, correction, affirmation, restriction, sequencing, equalization, and summing) and seven types of subordinate conjunctions (causation, requirements, objectives, highlighting, timing, engagement, and comparison). Based on the data analysis, the researcher concluded that the more dominant conjunction found was coordinative conjunction following the substance of the magazine profile that is communicative.